FABRICATION AND IN VITRO CHARACTERIZATION OF A NOVEL NANOSUSPENSION OF TELMISARTAN: A POORLY SOLUBLE DRUG PREPARED BY ANTISOLVENT PRECIPITATION TECHNIQUE USING 33 FACTORIAL DESIGN - MOHAPATRA, PRASANTA KUMAR; SIREESHA; RATHORE, VAIBHAV; VERMA, HARISH CHANDRA; RATH, BIBHUTI PRASAD; SAHOO, SATYAJIT (International Journal of Applied Pharmaceutics, 2020)
Objective: The motivation behind the current examination was to build the solvency and dissolution rate of an antihypertensive drug telmisartan by the planning of nanosuspension by precipitation method at the research facility scale. We researched the nanoparticle manufacture of telmisartan employing a 33 factorial experimental configuration considering the impacts of nanosuspension on the physical, morphological, and dissolution properties of telmisartan. Methods: To get ready, nanosuspension particles of an ineffectively dissolvable drug are moreover of a drug solution to the anti-solvent leads to abrupt supersaturation and precipitation the making of nanoparticles. The nanosuspension particles of a poorly soluble drug loaded with urea and surfactants (sodium lauryl sulfate (SLS), poloxamer 188, Tween 80) have been prepared by a precipitation method. The nanosuspension particles were characterized for particle size, zeta potential, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), in vitro drug release, and release kinetics. Results: The readily optimized batch nanosuspension particles evaluated and exhibited the particle size (750 nm), zeta potential (-24.33 mV), differential scanning calorimetry (DSC) drug exhibited a change in crystalline form to amorphous, in vitro dissolution (F12 was higher 95% within 5 min) and drug release kinetics. The formulation parameter of surfactant concentration is optimized. Conclusion: The formulation of the nanosuspension approach has been shown to substantial improvement in the dissolution rate, thereby enhancing the oral bioavailability with the future development of this technology.